Komunikasi Antarpribadi Generasi Z Dalam Mengatasi Depresi Di Masa Pandemi (Kecamatan Tajurhalang) - Yudha Febri Al Paksi; Muhammad Ichsan; Lukman; Muhammad Faizal (Journal of Innovative and Creativity, 2025)
This study aims to determine Generation Z's interpersonal communication in dealing with depression during pandemic the Kec. Tajurhalang, as well as understanding the interpersonal communication barriers of Generation Z in dealing with depression during pandemic in Kec. Tajurhalang. The research design uses descriptive qualitative research methods, with the Miles & Huberman interactive analysis model consisting of data collection, data reduction, data presentation, conclusions. The results of this study indicate that the Z generation in Kec. Tajurhalang tends to carry out the role of interactional type of interpersonal communication (The Interactional View) and self- disclosure face-to-face or via WhatsApp. The existence of a pandemic caused Generation Z in Kec. Tajurhalang feels the symptoms of depression in terms of psychological, physical and social life influences. These symptoms make obstacles and obstacles for generation Z, Kec. Tajurhalang in communicating and socializing during a pandemic.